1999
DOI: 10.3168/jds.s0022-0302(99)75408-1
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Carbohydrate and Protein Sources on Fermentation and Passage Rates in Dairy Cows,,

Abstract: Four ruminally cannulated Holstein cows in midlactation were randomly assigned to a 4 x 4 Latin square design with a 2 x 2 factorial arrangement of treatments to evaluate two nonstructural carbohydrate sources (corn or barley) with two sources of ruminally undegradable protein (soybean meal or extruded soybean meal) on milk production, ruminal fermentation, and digesta passage rates. Milk production (25.1, 27.5, 23.8, and 23.5 kg/d for the corn and soybean meal, corn and extruded soybean meal, barley and soybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
75
2
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 31 publications
13
75
2
5
Order By: Relevance
“…French and Kennelly (1990) observed that when concentrates were fed to Holstein cows in 12 equal portions at 2-h intervals compared to two equal portions, the higher feeding frequency tended to elevate ruminal pH, increase acetate:propionate ratio and milk fat percentages. When lactating cows were supplemented with protein concentrate either two or five times daily, average rumen pH was higher and propionate lower in cows supplemented with five meals (Casper et al 1999). Muller et al (1980) observed that lactating cows produced 10% more CH 4 (% of GEI) in response to feeding concentrates six times daily compared to when they were fed twice daily.…”
Section: Feeding Frequencymentioning
confidence: 99%
“…French and Kennelly (1990) observed that when concentrates were fed to Holstein cows in 12 equal portions at 2-h intervals compared to two equal portions, the higher feeding frequency tended to elevate ruminal pH, increase acetate:propionate ratio and milk fat percentages. When lactating cows were supplemented with protein concentrate either two or five times daily, average rumen pH was higher and propionate lower in cows supplemented with five meals (Casper et al 1999). Muller et al (1980) observed that lactating cows produced 10% more CH 4 (% of GEI) in response to feeding concentrates six times daily compared to when they were fed twice daily.…”
Section: Feeding Frequencymentioning
confidence: 99%
“…Nonetheless, under practical farming conditions dairy operations utilise only approximately 25% of the dietary N for milk, weight gain and foetal growth (Børsting et al, 2003). Numerous dietrelated factors can influence N efficiency, such as overfeeding with rumen degradable protein (Hristov et al, 2004), lack of synchronisation between ruminal carbohydrate and protein degradation (Casper et al, 1999), unbalanced composition of amino acids absorbed in the small intestine (Rulquin et al, 1993) and undersupply of -E-mail: nbk@agrsci.dk nutrients other than amino acids (Firkins et al, 2006). However, N efficiency is influenced by not only dietary factors but also the production level of the cow and the inevitable endogenous amino acid catabolism influences overall efficiency (Lobley, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Considerando que a eficiência alimentar foi similar entre as dietas (TABELA 3), uma possível causa de redução na produção de leite em dietas à base de cevada (DBC) poderia ser a menor ingestão de matéria seca, em especial de amido, e conseqüentemente de EL l . CASPER et al (1999) especularam que o maior conteúdo de amido do milho em relação à cevada pode contribuir para uma produção maior de leite em dietas à base de milho (DBM). A produção de leite corrigido para 4% de gordura (LCG), também decresceu linearmente (P<0,01), na ordem de 0,012 kg de leite para cada 1% de acréscimo na substituição de milho triturado por cevada laminada (TABELA 4 e GRÁFICO 2).…”
Section: Methodsunclassified
“…Por outro lado, KENNELLY et al (2001) relataram que a substituição do milho pela cevada na dieta de vacas em lactação pode resultar na queda do pH ruminal, redução da digestão da fibra, da ingestão de matéria seca (IMS) e depressão da gordura do leite. Além disto, CASPER et al (1999) relataram diminuição na produção de leite e IMS em relação ao peso vivo devido à substituição do milho pela cevada. Geralmente a adição de cevada à dieta reduz a digestibilidade total de todas as frações dos alimentos (OVERTON et al, 1995;OROZCO-HERNÁNDES et al, 1997).…”
Section: Introductionunclassified
See 1 more Smart Citation